The impact of metabolic comorbidities and alcohol consumption on FIB-4 and NFS performance in MAFLD: A multicentric preliminary data. (March 2023) - Cespiati, A.; Lombardi, R.; Smith, D.; Carvalhana, S.; Cinque, F.; Policarpo, S.; Bertelli, C.; Pisano, G.; Fracanzani, A.L.; Cortez-Pinto, H.
Abstract : Background/Aims: Metabolic dysfunction-associated fatty liver disease (MAFLD) is defined by liver steatosis with metabolic comorbidities, with different degree of disease severity. Fibrosis-4 Index (FIB-4) and NAFLD fibrosis score (NFS) are non-invasive tests (NITs) of fibrosis widely used in NAFLD, while FibroScan®, by liver stiffness measurement (LSM), evaluate the fibrosis degree. Aims: to evaluate in patients with MAFLD the performance of scores in comparison with LSM and to define the impact of metabolic comorbidities and alcohol intake on NITs performance. Method: 600 patients with MAFLD referring to liver clinic in Lisbon and Milan. Clinical, laboratory data and FibroScan® were performed. LSM≥10/9.3kPa for M/XL probes suggested advanced fibrosis. Daily alcohol consumption: abstainers, low (<30/20gr), moderate (30-40 and 20-30gr) and heavy (≥40/≥30gr) for men and women respectively. FIB-4<1.45 and NFS<-1.455 ruled out advanced liver fibrosis while FIB-4>3.25 and NFS>0.676 rule in. Results: Mean age 54 yrs, 60% male, 54% obese, 30% diabetic. 61% abstainers, 13% had moderate-high alcohol consumption. LSM≥10 kPa in 15%, FIB-4<1.45 in 74%, FIB-4>3.25 in 4% and indeterminate in 22%, NFS<-1.455 in 70%, NFS>0.676 in 2% and indeterminate in 28%. Compared to LSM, FIB-4 and NFS had AUROCs of 0.58 and 0.52 for advanced fibrosis and of 0.66 and 0.72 for the exclusion. For both detection and exclusion of advanced fibrosis, FIB-4 performed worse in obese versus non-obese (AUROCs 0.55vs0.63; AUROCs 0.64vs0.72), while no differences were found regarding NFS (AUROCs 0.51vs0.52; AUROCs 0.71vs0.70). FIB-4 and NFS performed poorly in T2DM for advanced fibrosis (AUROCs<0.60). There was a negative impact of alcohol consumption on diagnostic performance for advanced liver fibrosis, particularly for NFS (AUROCs 0.50 for high alcohol). Conclusion: Metabolic comorbidities and alcohol consumption negatively impact the ability of NITs in identifying advanced fibrosis in MAFLD. Revision of values may be necessary to avoid misdiagnosis in patients with advanced liver disease.